Соціокультурна місія канадського Центру української культури та освіти "Осередок" (друга чверть ХХ – початок ХХІ ст.) - Бодруг, А. (Чорноморська минувшина, 2020)
Мета даної наукової статті полягає у розгляді діяльності Центру української культури та освіти «Осередок» та теоретичного обґрунтування його внеску у процеси збирання, дослідження, збереження та подальшого експозиціонування історичної, культурної та духовної спадщини української діаспори Канади. Саме об’єднання зусиль суспільно-політичних організацій та відомих громадських діячів заклало важливу підвалину в збереження нації в тяжких воєнних та соціальних умовах перебування на чужині. «Осередок» став не лише взірцем українознавчої освіти, але і важливим центром розбудови українсько-канадських відносин, а також загалом вплинув на розвиток канадської культури. Для досягнення зазначеної мети було залучено необхідну кількість джерел та історіографічної літератури, які торкались різних аспектів проблеми. Автором було застосовано такі загальноісторичні наукові методи дослідження, як історико-генетичний, історико-порівняльний та історико-типологічний. У межах даного дослідження було надано генезис Центру української культури та освіти «Осередок», розглянуто основні підрозділи, напрямки роботи, соціокультурні програми, типологізовано найважливіші колекції й архівні документи, а також проаналізовано їх історико-культурну цінність. Окрема увага присвячена аналізу ролі засновників, збирачів колекцій та меценатів у розвитку «Осередку». Вперше здійснена спроба узагальнення різних аспектів порушеної проблеми. The purpose of this article is to consider the activities of the Ukrainian Cultural and Educational Center «Oseredok» and the theoretical justification of its contribution to the collection, research, preservation and exhibition of historical, cultural and spiritual heritage of the Ukrainian diaspora in Canada. «Oseredok» became not only a model of Ukrainian studies education, but also an important center for the development of Ukrainian-Canadian relations, and also influenced the development of Canadian culture in general. To achieve this goal, the necessary number of sources and historiographical literature touched on various aspects of the problem were examined. Such general historical scientific research methods as historical-genetic, historical-comparative and historical-typological were used. The relevance of this study is related to the modern national-cultural movement, which is embodied in the activities of organizations, art, educational and scientific centers, the introduction of new Ukrainian festivals, the study of previously classified, archival documents. Some aspects of this problem were revealed in the works of such researchers as: Jus O. V., Matyash I. B., Solonskaya N. G. and Priymak T. M. However, in our opinion, the monument protection and sociocultural activities of the Ukrainian Cultural and Educational Center «Oseredok» is worth more indepth research. Thus, the Ukrainian Cultural and Educational Center «Oseredok» was the unifying force that brought together under one cultural cover Ukrainians with different religious beliefs, political views and values. The founders and patrons of the «Oseredok» were prominent Ukrainian figures: O. Koshetz, T. Koshetz, P. Matsenko, M. Mandryka, T. Pavlychenko, P. Yuzyk, V. Kossar, M. Marunchak, J. Rudnytsky and others. For 76 years, Oseredok has become the guarantor of the collective memory of the Ukrainian people. Even the house of the organization, formerly the House of the Bible Society, has great spiritual power, which contributes to a noble socio-cultural mission. The versatility of the Center's activities, which includes archival, library, museum, educational and publishing work, is striking. The archive of the organization has the largest collection of documents, memoirs, photographs, maps in Canada, which covers the period of 16th - 20th centuries. Valuable are the documents and memoirs of I. M. Bobersky, E. M. Konovalets, the Koshets family, as well as a monument of the 18th century – Irmola by Georgy Tyapetsky. «Oseredok» has a rich library collection of more than 40 thousand volumes and 10 thousand periodicals. Nomocanon of the 17th century is a very rare book. The collection of the museum of the Center consists of 8 thousand exhibits, which includes objects of decorative and applied arts, musical instruments, church utensils, personal belongings. In the collections of the art gallery you can see paintings by more than 30 Ukrainian artists from realism to avant-garde. The Center has higher education courses that have brought up many prominent Ukrainians. The publishing activity of the center not only contributed to the development of science and art, but also acquainted the whole world with the rich Ukrainian culture. Thus, Ukrainian Cultural and Educational Centre «Oseredok» is a model of cultural preservation organization.